Migración Haitiana en tránsito por Ecuador (Coyuntura) - López Rivera, Andrés (2017)
This paper presents a preliminary analysis about Haitian migration in transit trough Ecuador. Its main objective is to evaluate the different dimensions of transit migration phenomena and problematize the concept as a category of analysis. In the first place, transit migration concept is exposed, highlighting its problematic aspects. Then, the author provides a general description of Haitian migration and the cases of Brazil, as destination country, and Ecuador, as transit country, are explored. Finally, some questions regarding the complex dynamic of transit migrations are posed taking into consideration the Haitian case.